Mechanism and Control of Meiotic DNA Double-Strand Break Formation in S. cerevisiae - Yadav, Vikash Kumar; Claeys Bouuaert, Corentin (Frontiers in Cell and Developmental Biology, 2021)
Developmentally-programmed formation of DNA double-strand breaks (DSBs) by Spo11 initiates a recombination mechanism that promotes synapsis and the subsequent segregation of homologous chromosomes during meiosis. Although DSBs are induced to high levels in meiosis, their formation and repair are tightly regulated to minimize potentially dangerous consequences for genomic integrity. In S. cerevisiae, nine proteins participate with Spo11 to catalyze DSB formation, but their molecular functions have been challenging to define. Here, we describe our current view of the mechanism of meiotic DSB formation based on recent advances in the characterization of the structure and function of DSB proteins and discuss regulatory pathways in the light of recent models.